Erratum: An analysis of the influence of the accelerator/sulfur ratio in the cure reaction and the uniaxial stress-strain behavior of SBR - Marzocca, Angel José (2004)
Vulcanized styrene butadiene rubber (SBR) with different cure systems was prepared and analyzed by using the model of rubber elasticity based on the tube concept, applied to the treatment of the stress-strain measurements. Samples with several ratio accelerators to sulfur, Λ, between 0.22 and 3.0 cured at 433 K were studied. The network chain density and the crosslink density of the samples were evaluated. By means of normalized rheometer curves, the kinetics of cure of these samples were evaluated by considering the model of isothermal curing proposed by Kamal and Sourour. In this frame, the parameters of the kinetics model were obtained. A correlation between the order of the kinetic equation, n, and the network chain density of the cure samples was established.